FAMILY BIBIONIDAE - Falaschi, Rafaela Lopes; Oliveira, Sarah Siqueira; Amorim, Dalton De Souza (Zootaxa, 2016)
The Bibionidae are a family belonging to the suborder Bibionomorpha with four genera and 17 species known from Colombia. This work expands the distribution of these species to other localities in the country.